The Assessment Practices by Content-faculty, Student-teaching Supervisor and Cooperating Mentors of Pre-professional Mathematics Teachers in State Universities in Cagayan Valley Region in the Philippines â€ - MARIO Colega Oli (LPPM Universitas Negeri Jakarta, 2018)
Assessment is the process of teachers gathering information about studentsâ€™ learning, including their achievement and behavior in both the cognitive and affective domains enabling teachers to make informed decisions for classroom instruction. The Pre-professional Math Teachers were exposed with various assessment practices during their academic years which were implemented by their Professors across their academic subject and not to exclude Mathematics classes. Assessment was just regarded as a means for â€œgradingâ€ the mathematical skills and knowledge of the students and not to measure what is worth measuring. This study aimed to determine the assessment practices of content faculty, student-teaching supervisors and cooperating mentors of pre-professional mathematics teachers in State Universities in the Cagayan Valley Region in the Philippines It made used of the qualitative-quantitative research method and utilized questionnaires and semi-structured interview. Frequencies, means, standard deviation, and one-way analysis of variance were used. It was found out that Mathematics content faculty used conceptual class discussions or recitations, studentsâ€™ calculator and computer use, routine homework or drills, studentâ€™s use of manipulatives to monitor the learning progress of their students while write up of projects, tests (prelim, midterms, finals), and critique papers are utilized for grading purposes. The Student teaching Supervisors always used standard checklist for demonstration teaching, and post-conference and the Cooperating mentors used formal visit and post conference with the Pre-service Math Teachers for formative assessment in assessing the pedagogical skills of the Student teachers during the practicum period. Formal visits, standard checklists for demonstration teaching, and post-conferences with concerned individuals were utilized by both for summative assessment.